Ethnobotanical Study of Seaweed Utilization Among Local Communities in Muar, Johor - Mohd Sharimshah, Abdullah Lutfi; Furzani Pa’ee, (Enhanced Knowledge in Sciences and Technology, 2024)
This ethnobotanical study delves into the diverse utilization of seaweeds among the local community of Parit Jawa, Muar, Johor. The research aimed to identify and document the different categories of seaweeds utilized by the community, focusing on their applications in food, medicine, and other purposes. The objectives further included measuring the significance level of these seaweed groups are and their utilization within the local context. The study conducted online questionnaire interviews with respondents from Parit Jawa to gather comprehensive data. Results uncovered three primary categories of seaweeds: green, red, and brown. Notably, the green seaweed emerged as the most prominently cited among the locals. The blade part of the seaweed stood out as the most utilized component, primarily for culinary purposes. Utilizing Relative Frequency of Citation (RFC) and Cultural Significance Index (CSI) for analysis, the study highlighted the paramount importance of green seaweed in the daily activities of the Parit Jawa community. Locals acknowledged its abundant presence and frequent use for both sustenance and medicinal applications within the region. This research underscores the multifaceted uses and significance of seaweeds in the daily lives of Parit Jawa's community. It suggests avenues for further exploration into the specific and nuanced applications of these distinct seaweed categories, contributing to a deeper understanding of their role in the community's traditional practices and livelihoods.